1995
DOI: 10.1007/bf00294712
|View full text |Cite
|
Sign up to set email alerts
|

Modified treatment of early gastric cancer: Evaluation of endoscopic treatment of early gastric cancers with respect to treatment indication groups

Abstract: The results of endoscopic treatment of early gastric cancers were evaluated. The lesions were divided into two groups: the group with an absolute indication (AI) and the other with a relative indication (RI) for endoscopic treatment. Endoscopic mucosal resection (EMR) was performed on 106 lesions in 104 patients. In addition, 108 patients were treated by laser irradiation (LI). The status of the patients were serially assessed during the postoperative period. The residual rate in AI patients who underwent EMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 6 publications
1
35
0
3
Order By: Relevance
“…With strict selection criteria, a cumulative curative rate of 98.4% has been reported [40]. According to Maekawa et al [25], the best results would be expected in patients who have tumors of the differentiated type measuring 20 mm or smaller without depression, since lymph node metastases were rare in these variants.…”
Section: Discussionmentioning
confidence: 99%
“…With strict selection criteria, a cumulative curative rate of 98.4% has been reported [40]. According to Maekawa et al [25], the best results would be expected in patients who have tumors of the differentiated type measuring 20 mm or smaller without depression, since lymph node metastases were rare in these variants.…”
Section: Discussionmentioning
confidence: 99%
“…The five-year survival rate was 86%, a rate similar to more aggressive surgical approaches [58] . Hiki et al [59] reported a recurrence rate of 4.2% in their series. The main disadvantage of endoscopic methods is the risk of incomplete tumor resection.…”
Section: B Amentioning
confidence: 85%
“…The value of EMR and ESD has been proven effective in the management of early gastric cancer in several retrospective and prospective cohort studies but lack of high quality randomized controlled trial remains a challenge before routine use of this approach worldwide (52)(53)(54)(55)(56)(57). Considering that bleeding risk does not differ between ESD and EMR and that the perforation risk does not usually lead to life-threatening disease, therefore the benefit of ESD can outweigh the overall harm when compared with EMR with the proviso that that the ESD is performed by experienced practitioners (58).…”
Section: Endoscopic Approaches For the Management For Gastric Cancer mentioning
confidence: 99%